Brazo articulado controlado por voz para rehabilitación motora de personas discapacitadas del miembro superior - Carbajal Moran, Hipólito (2021)
The objective was to design an articulated arm with control of trajectory and speed by voice commands, to rehabilitate people with motor disabilities of the upper limb. The systemic method was used; voice commands were considered inputs to the system; movements of the arm link joints were considered outputs. From the tests carried out with the design, it was determined that the controller activated by voice commands allows to keep controlled the speeds of the different motors that make up the wrist, elbow and shoulder joints; With respect to the speeds, these are closely correlated, whose coefficients are greater than 0.99, which indicates that the difference between the desired speeds and those obtained have very little difference. In conclusion, an arm with articulations of three degrees of freedom was implemented, commanded by voice using pre-established codes, allowing the trajectories of the different characteristic movements of the arm to be described in a controlled manner, with displacements that generate rotation-elongation of the shoulder in the interval of 0° to 120°, elbow in the range of 0° to 120° and wrist movements from -30° to 60°; to rehabilitate people with motor disabilities of the upper limb.